An infectious viroid RNA replicon evolved from an in vitro-generated non-infectious viroid deletion mutant via a complementary deletion in vivo. - Wassenegger, M (1994)
The 359 nucleotides (nt) long potato spindle tuber prototype viroid (PSTVd) is sensitive to experimentally introduced mutations as the substitution or deletion of a single nucleotide usually abolishes its infectivity, although certain sequence alterations are tolerated. This is illustrated by the fact that viroid progeny can evolve in planta upon inoculation with substitution mutants generated in vitro, and by the existence of genetically stable 356-360 nt long PSTVd field isolates. However, to date, no viable in vitro-generated deletion mutant of PSTVd has been reported. We have now found a 341 nt long infectious PSTVd RNA replicon that evolved in agrotransformed plants transformed with the dimeric form of an in vitro-deleted, non-infectious 350 bp long PSTVd cDNA unit by an additional complementary deletion of 9 nt in vivo. This is the first report that the deletion-abolished infectivity of a viroid is restored by an additional deletion that concurrently restabilized its perturbed secondary structure by abandoning an internal segment of the rod-like molecule. The fact that approximately 5% of the total PSTVd RNA genome was deleted demonstrates that the maintenance of this viroid-specific rod-like structure is not only essential for nuclease protection but also for the infectivity, i.e. transmissibility, replicability, processibility and pathogenicity of these minimal infectious agents.